Rash after measles vaccination: laboratory analysis of cases reported in São Paulo, Brazil - Oliveira Maria I; Curti Suely P; Figueiredo Cristina A; Afonso Ana MS; Theobaldo Márcia; Azevedo Raymundo S; Durigon Edison L (Universidade de São Paulo, 2002)
OBJECTIVE: The clinical differential diagnosis of rash due to viral infections is often difficult, and misdiagnosis is not rare, especially after the introduction of measles and rubella vaccination. A study to determine the etiological diagnosis of exanthema was carried out in a group of children after measles vaccination. METHODS: Sera collected from children with rash who received measles vaccine were reported in 1999. They were analyzed for IgM antibodies against measles virus, rubella virus, human parvovirus B19 (HPV B19) using ELISA commercial techniques, and human herpes virus 6 (HHV 6) using immunofluorescence commercial technique. Viremia for each of those viruses was tested using a polimerase chain reaction (PCR). RESULTS: A total of 17 cases of children with exanthema after measles immunization were reported in 1999. The children, aged 9 to 12 months (median 10 months), had a blood sample taken for laboratory analysis. The time between vaccination and the first rash signs varied from 1 to 60 days. The serological results of those 17 children suspected of measles or rubella infection showed the following etiological diagnosis: 17.6% (3 in 17) HPV B19 infection; 76.5% (13 in 17) HHV 6 infection; 5.9% (1 in 17) rash due to measles vaccine. CONCLUSIONS: The study data indicate that infection due to HPV B19 or HHV 6 can be misdiagnosed as exanthema due to measles vaccination. Therefore, it is important to better characterize the etiology of rash in order to avoid attributing it incorrectly to measles vaccine.